HIGH-ACCURACY MAGNETIC FIELD MEASUREMENTS ON COOL GIANT beta GEMINORUM - Baklanova, D. N.; Plachinda, S. I. (Одеські астрономічні публікації, 2010)
Pollux is a weakly-active yellow gi ant neighbor of the Sun with known regular surface magnetic field about 1 Gauss. We present new high- accuracy magnetic field measurements of β Gem which were obtained during 2010 at Crimean Astrophysical Observatory with 2.6-m telescope and Stokesmeter.